TRAJECTORY PLANNING AND SIMULATION OF A 6-DOF ROBOTIC MANIPULATOR - Magraoui, Rabah; Hadi, Osmani El; Mohammed, Ouali (Veredas do Direito, 2026)
This study presents the modelling, simulation, and validation of trajectory planning for a six-degree-of-freedom (6-DOF) robotic manipulator operating in constrained industrial environments. Linear, circular, and helical trajectories were generated and analyzed in Cartesian and joint spaces using the Denavit–Hartenberg formulation and Paul’s analytical inverse kinematic method. To improve motion smoothness and reduce actuator stress, polynomial interpolation techniques were implemented and compared. Quintic interpolation reduced jerk peaks by approximately 68% compared with cubic interpolation while maintaining stable velocity and acceleration profiles. An obstacle-avoidance strategy based on a cylindrical obstacle was also introduced along the helical trajectory. Simulations performed using MATLAB and SolidWorks demonstrated smooth and continuous robot motion without singularities or abrupt deviations. Validation against reference robotic models showed excellent agreement with published results, with a root mean square error (RMSE) below 1.2×10−4 rad and an average computation time lower than 0.015 s per trajectory point. The proposed methodology provides accurate and collision-free trajectory planning suitable for advanced robotic applications such as welding, drilling, and automated assembly.